Experiential Retail in the Smartphone Industry: Consumer Behaviour and Brand Loyalty - Joshi, Mudit; Mathur, Disha (Mercados y Negocios, 2025)
The goal of this study is to examine the impact of experiential retail on purchasing decisions and brand loyalty in the smartphone industry. The present research executes a quantitative analysis utilising the SPSS version 23 software package. A structured questionnaire survey technique is employed to gather the data from the experiential retailers in the smartphone industry. A purposive sampling strategy has been adopted for analysis. The objective behind this technique is to gather data on the perception of experiential retailers regarding the impact of purchasing decisions and brand loyalty in the smartphone industry. Descriptive statistics, ANOVA, regression and Pearson correlation analysis are performed in research. The study’s outcomes indicate that experiential retail shopping has a significant impact on the growth and sustainability of consumers in the smartphone industry. Furthermore, the study also evaluates the considerable effects of consumers’ behaviours in the smartphone industry through purchasing decisions and brand loyalty. The study recommends that experiential retailers enhance their innovative strategies to strengthen their business in the smartphone industry.